Serum Soluble ST2 Correlated with Symptom Severity and Clinical Response of Sublingual Immunotherapy for House Dust Mite-Induced Allergic Rhinitis Patients - Kang Zhu; Cui Xia; Jingguo Chen; Chao Yu; Tianxi Gao; Jing Yan; Na Shao; Pin Zhu; Bin Sun; Xiaoyong Ren; Yanni Zhang (Hindawi Limited, 2021)
Background. Suppressor of tumorigenicity 2 (ST2) is a key biomarker in inflammation and cardiovascular diseases, but limited data is available on its role in allergic rhinitis (AR). Objective. The aim of this study is to explore the role of serum soluble ST2 (sST2) in evaluating disease severity and predicting the efficacy of sublingual immunotherapy (SLIT) in house dust mite- (HDM-) induced AR patients. Methods. Eighty healthy controls (HC group) and 160 HDM-induced AR patients, including 40 mild patients (MAR group) and 120 moderate-severe patients (MSAR group), were recruited in this study. Serum was collected from all participants and levels of sST2 were determined by ELISA and the relationship between sST2 levels and disease severity was assessed. In the MSAR group, 109 patients received 3 years of SLIT, and the relationship between serum levels of sST2 and efficacy of SLIT was exampled. Results. Serum sST2 levels were increased in HDM-induced AR patients compared to the HC group (P<0.001), and the concentrations were higher in the MSAR group than in the MAR group and HC group (all P<0.05). Moreover, sST2 levels positively correlated with the total nasal symptom score (TNSS), visual analogue scale (VAS), and specific IgE levels (P<0.05). Seventy-eight MSAR patients accomplished SLIT, and they were divided into an effective group (n=40) and an ineffective group (n=38). The serum sST2 levels in the effective group were lower than those in the ineffective group (P<0.001). In addition, patients in the effective group levels exhibited significantly lower sST2 levels post-SLIT than pre-SLIT (P<0.001), but no statistic difference was observed in the ineffective group (P>0.05). Receiver operating characteristic (ROC) curve showed promising accuracy for predicting clinical efficacy of SLIT in AR patients (area under the curve=0.839, P<0.001). Conclusion. Serum sST2 is a potential biomarker for assessing disease severity and may serve as a sensitive biomarker for predicting the therapeutic response of SLIT in HDM-induced AR patients.